RESEPSI PEMBACA SASTRA ARAB DIGITAL: STUDI NOVEL “MIN ‘ĀLAM ĀKHAR” PADA APLIKASI WATTPAD - Rohmah, Alfia; Kusumawati, Aning Ayu (Sunan Kalijaga State Islamic University Yogyakarta, 2023)
The role of readers in responding to literary works is very important in determining the quality of literary works in the digital world, such as literary works written in the Wattpad application. Based on this, the researcher conducted research on reader reception of Min 'Ālam Ākhar's novel which was uploaded to the Wattpad application by the username Manjiro57 using Stuart Hall's theory which groups receptions into three categories, namely dominant-hegemonic position, negotiated position and oppositional position. The data in this study were obtained from the comments column on Min 'Ālam Ākhar's novel in the Wattpad application which were collected using the note-taking technique based on a purposive sampling technique. The data found were analyzed using descriptive-analytical methods. This research shows that the dominant-hegemonic position is found more often than the negotiated position or oppositional position. The existence of the dominant-hegemonic position means that this novel is enough to attract the attention of readers. The negotiated position can be a suggestion for novel writers to find out how the storyline that the reader wants. In the oppositional position, the readers provided comments related to several storylines which they think did not make sense.